2020
DOI: 10.1038/s41573-019-0056-x
|View full text |Cite|
|
Sign up to set email alerts
|

Next-generation influenza vaccines: opportunities and challenges

Abstract: Vaccination represents an efficient and cost-effective way to contain influenza epidemics and preserve public health. Since their introduction in the 1940s, seasonal influenza vaccines have saved countless lives and limited pandemic spread. Influenza viruses nonetheless continue to evolve through genetic mutation and escape from natural immunity, and vaccines must be updated yearly. The protective efficacy of the current licensed vaccines varies each year (Fig. 1a), depending on the antigenic match between cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
225
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(230 citation statements)
references
References 224 publications
0
225
0
5
Order By: Relevance
“…The inactivated virus vaccine may have lost the capability of the wild type virus to induce complete maturation and activation of dendritic cells, necessary to activate T cells optimally. Influenza vaccination not always induces satisfactory immunity and addition of an adjuvant compound to TIV was reported to increase immunogenicity (61)(62)(63). More recently, for this reason adjuvant-containing influenza vaccines have been introduced to increase influenza immunity in the aging population (64).…”
Section: Use Of Jak-stat Pathway Activity In Vaccine Developmentmentioning
confidence: 99%
“…The inactivated virus vaccine may have lost the capability of the wild type virus to induce complete maturation and activation of dendritic cells, necessary to activate T cells optimally. Influenza vaccination not always induces satisfactory immunity and addition of an adjuvant compound to TIV was reported to increase immunogenicity (61)(62)(63). More recently, for this reason adjuvant-containing influenza vaccines have been introduced to increase influenza immunity in the aging population (64).…”
Section: Use Of Jak-stat Pathway Activity In Vaccine Developmentmentioning
confidence: 99%
“…Unlike viral RNA, HA titer of H1N1 subtype was not changed by UV irradiations in this study (Figure 3). HA is a target for vaccines for IAVs because antibodies against HA are a major component of the human immune response and influenza vaccination [35]. Some studies showed that UV-inactivated viruses, including coronaviruses, were useful for the vaccines [36,37], but the studies about vaccines using UV-inactivated influenza viruses were scarcely reported [38].…”
Section: Discussionmentioning
confidence: 99%
“…Despite influenza vaccines being available, the high rate of mutation requires a constant redesign. 101 , 102 The versatile application of peptide microarrays in unraveling epitope-specific antibody responses, drug and vaccine development approaches for influenza are highlighted by several studies. 50 55 …”
Section: Application Of Peptide Microarrays For Pandemic Diseasesmentioning
confidence: 99%